Integrin alpha v beta 3 rescues melanoma cells from apoptosis in three-dimensional dermal collagen. - Montgomery, A M (1994)
Human melanoma cells required ligation of the integrin alpha v beta 3 to sustain viability and growth in three-dimensional dermal collagen. Variant melanoma cells, lacking the alpha v subunit, progressed rapidly to apoptosis within this matrix, whereas transfection of these cells with an alpha v cDNA restored alpha v beta 3 expression and prevented apoptosis. Furthermore, inhibition of alpha v beta 3 ligation with a monoclonal antibody promoted cell death. Apoptosis of alpha v(-) cells within this matrix could be overcome by the addition of insulin or serum. However, alpha v(+) melanoma cells had a significant growth advantage in the presence of these growth factors. Initial adhesion of the melanoma cells to type I collagen depended on ligation of alpha 2 beta 1, but these cells can degrade this collagen to expose cryptic alpha v beta 3 binding sites. These findings provide evidence that the survival and growth of transformed cells may be regulated by collagen degradation and integrin-dependent anchorage to this proteolysed matrix.